Simulation of Long-term Yield and Soil Water Consumption in Apple Orchards on the Loess Plateau, China, in Response to Fertilization - Xingxing Peng (Nature Portfolio, 2017)
Abstract The Loess Plateau, China, is the world’s largest apple-producing region, and over 80% of the orchards are in rainfed (dryland) areas. Desiccation of the deep soil layer under dryland apple orchards is the main stressor of apple production in this region. Fertilization is a factor that causes soil desiccation in dryland apple orchards. Given its applicability and precision validations, the Environmental Policy Integrated Climate (EPIC) model was used to simulate the dynamics of fruit yield and deep soil desiccation in apple orchards under six fertilization treatments. During the 45 years of study, the annual fruit yield under the fertilization treatments initially increased and then decreased in a fluctuating manner, and the average fruit yields were 24.42, 27.27, 28.69, 29.63, 30.49 and 29.43 t/ha in these respective fertilization treatments. As fertilization increased, yield of the apple orchards increased first and then declined,desiccation of the soil layers occurred earlier and extended deeper, and the average annual water consumption, over-consumption and water use efficiency increased as fertilization increased. In terms of apple yields, sustainable soil water use, and economic benefits, the most appropriate fertilization rate for drylands in Luochuan is 360–480 kg/ha N and 180–240 kg/ha P.